A dibenzo[a, c]phenazine-11, 12-dicarbonitrile (DBPzDCN) acceptor based thermally activated delayed fluorescent compound for efficient near-infrared electroluminescent devices. Issue 25 (13th June 2018) - Wang, Shipan; Miao, Yang; Yan, Xianju; Ye, Kaiqi; Wang, Yue
Abstract : A high external quantum efficiency of 7.68% was achieved in a near-infrared organic light-emitting diode with a novel TADF molecule. Abstract : In this paper, a near-infrared (NIR) TADF molecule with dibenzo[ a, c ]phenazine-11, 12-dicarbonitrile (DBPzDCN) as the acceptor has been designed, synthesized and characterized. Connecting the DBPzDCN core with a diphenylamine (DPA) donor, NIR emission is successfully achieved. The relationship between the molecular structure and optoelectronic properties is discussed experimentally and theoretically. A high external quantum efficiency (EQE) of 7.68% with an emission peak at 698 nm and Commission Internationale de L' Eclairage (CIE) coordinates of (0.68, 0.30) was achieved in a NIR organic light-emitting diode.